Tethered Oral Tissue Release Among Breastfed Infants: Maternal Experiences. (7th June 2021) - Winkel, Taylor; Wilson, Jennifer; Spence, Marsha; Colby, Sarah; Springer, Cary; Hedrick, Mark; Kavanagh, Katie
Abstract: Objectives: The objective was to explore mothers' experiences breastfeeding/chestfeeding an infant diagnosed with an issue with tethered oral tissue(s), for which surgical intervention was performed (i.e., tissue was "released"). Methods: This was a cross sectional, observational survey conducted online from August to September 2020. Recruitment occurred via social media. Mothers of infants <12 months of age were eligible to participate if (1) the mother was >18 years of age, (2) they had breastfed/chestfed or were currently breastfeeding/chestfeeding their infant, and (3) the infant had >1 tethered oral tissue released. The survey included demographic and breastfeeding/chestfeeding questions as well as questions about tethered oral tissue concerns/resolution. Results: Of 479 screens, 226 were eligible and 115 consented to participate. Ninety-three responses were considered valid and complete. The sample was homogeneous in terms of maternal race (95% white), marital status (94% married/cohabitating), and breastfeeding status (89% providing breastmilk at time of survey). Eighty-seven (94%) mothers reported lingual frenum release; 81 (87%) reported labial frenum release; and 16 (17%) reported buccal frenula release. Seventy-four (80%) mothers reported more than one tissue was released; most frequently, this included the lingual and labial frenula ( n = 58; 62%). Most mothers felt "very confident" in their ability to identify which tissues were released: lingual (94%); labial (97%); and buccal (82%). Lactation consultants were the most frequently identified source of information about tethered oral tissues (62% of mothers) and treatment referrals (42%), while pediatric dentists were most likely to perform the intervention (66%). Nearly all participants ( n = 82; 88%) reported feeding improvement, post-release. Conclusions: Results indicate lactation consultants are frequently serving as both information and referral sources for release of tethered oral tissues, while pediatric dentists are most frequently performing the release. Despite limited evidence supporting release of tethered oral tissues for infant-feeding concerns, mothers in this study reported multiple tissues were released and that feeding was positively affected. Funding Sources: Internal professional development funds.